1995
DOI: 10.1038/376236a0
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic resonance without tuning

Abstract: Stochastic resonance (SR) is a phenomenon wherein the response of a nonlinear system to a weak periodic input signal is optimized by the presence of a particular, non-zero level of noise. SR has been proposed as a means for improving signal detection in a wide variety of systems, including superconducting quantum interference devices, and may be used in some natural systems such as sensory neurons. But for SR to be effective in a single-unit system (such as a sensory neuron or a single ion channel), the optima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
435
1
3

Year Published

1998
1998
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 764 publications
(475 citation statements)
references
References 27 publications
21
435
1
3
Order By: Relevance
“…When single-electron boxes are not connected to each other, electron tunneling occurs independently in each box's junction. As in the work of Collins et al [3], we apply a common input to all the boxes and calculate the summation of the outputs of all the boxes. For simplicity, we apply a common spike train S in of frequency f to all the boxes, and rather than consider practical circuits that calculate the summation of box outputs 1 .…”
Section: Neuron Circuit With Single-electron Boxmentioning
confidence: 99%
See 1 more Smart Citation
“…When single-electron boxes are not connected to each other, electron tunneling occurs independently in each box's junction. As in the work of Collins et al [3], we apply a common input to all the boxes and calculate the summation of the outputs of all the boxes. For simplicity, we apply a common spike train S in of frequency f to all the boxes, and rather than consider practical circuits that calculate the summation of box outputs 1 .…”
Section: Neuron Circuit With Single-electron Boxmentioning
confidence: 99%
“…Oya et al proposed a single-electron competitive neural network and demonstrated that the network operated correctly when T ≤ 1 K [5]. In this paper, we propose a single-electron neural circuit that can operate at high temperature by exploiting stochastic resonance (SR) in an ensemble of spiking neurons [3].…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely recognized that noise is able to facilitate the information processing and enrich the inherently stochastic dynamics of neural systems (Deco et al 2009;Destexhe and Contreras 2006). Two fundamental and maybe the most important mechanisms that the neural system may use to enhance its information transmission capability with the help of noise are stochastic resonance (Collins et al 1995;Gailey et al 1997;Chialvo et al 1997;Lee and Kim 1999;Chik et al 2001;Guo and Li 2009) and coherence resonance (Guo and Li 2009;Pikovsky and Kurths 1997;Lindner et al 2002;Li and Gao 2008;Sun et al 2008). For each mechanism, the response of the neural system greatly depends on the noise intensity, and there exists a maximal neural response at an optimal noise level.…”
Section: Introductionmentioning
confidence: 99%
“…The stochastic part of a signal is usually thought of as`noise' and is the part any system tries to get rid of. In stochastic resonance theory (Collins, Chow & Imhoff, 1995;Gammaitoni, Ha Ènggi, Jung & Marchesoni, 1998), noise is hypothesized to be useful, but an application of the theory to the neuronal system tells us that it only works inside a very limited parameter region and a carefully adjusted input signal is required (Feng & Tirozzi, 2000). Another possible role played by noise in neuronal systems has been reported recently: we (Feng & Zhang, 2001) have numerically demonstrated that with the help of noise, a neuron, such as the HH and the FHN model, can increase its efferent ®ring rate when inhibitory inputs increase.…”
Section: Introductionmentioning
confidence: 99%